AMPK phosphosite profiling by label-free mass spectrometry reveals a multitude of mTORC1-regulated substrates - William J. Smiles; Ashley J. Ovens; Dingyi Yu; Naomi X. Y. Ling; Andrea C. Poblete Goycoolea; Kaitlin R. Morrison; Emmanuel O. Murphy; Astrid Glaser; Sophie F. Monks O’Byrne; Scott Taylor; Alistair M. Chalk; Carl R. Walkley; et al. (npj Metabolic Health and Disease)
Abstract The nutrient-sensitive protein kinases AMPK and mTORC1 form a fundamental negative feedback loop that governs cell growth and proliferation. mTORC1 phosphorylates α2-S345 in the AMPK αβγ heterotrimer to suppress its activity and promote cell proliferation under nutrient stress conditions. Whether AMPK contains other functional mTORC1 substrates is unknown. Using mass spectrometry, we generated precise stoichiometry profiles of phosphorylation sites across all twelve AMPK complexes expressed in proliferating human cells and identified seven sites displaying sensitivity to pharmacological mTORC1 inhibition. These included the abundantly phosphorylated residues β1-S182 and β2-S184, which were confirmed as mTORC1 substrates on purified AMPK, and four residues in the unique γ2 N-terminal extension. β-S182/184 phosphorylation was elevated in α1-containing complexes relative to α2, an effect attributed to the α-subunit serine/threonine-rich loop. Mutation of β1-S182 to non-phosphorylatable Ala had no effect on basal and ligand-stimulated AMPK activity; however, β2-S184A mutation increased nuclear AMPK activity, enhanced cell proliferation under nutrient stress and altered expression of genes implicated in glucose metabolism and Akt signalling. Our results indicate that mTORC1 directly or indirectly phosphorylates multiple AMPK residues that may contribute to metabolic rewiring in cancerous cells.